2014
DOI: 10.3892/or.2014.3626
|View full text |Cite
|
Sign up to set email alerts
|

Isoquercitrin inhibits the progression of pancreatic cancer in vivo and in vitro by regulating opioid receptors and the mitogen-activated protein kinase signalling pathway

Abstract: Pancreatic cancer is a common malignant tumour that affects individuals worldwide. In recent years, the incidence and mortality rates of pancreatic cancer have continuously increased. Currently, the primary clinical treatment methods for pancreatic cancer include surgical resection, chemotherapy and radiotherapy. However, these treatment methods rarely produce satisfactory therapeutic outcomes. Extensive research has also proven that the effective components of several traditional Chinese medicines, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…It described new Wnt pathway regulation mechanisms, which may be responsible for the induction of colorectal cancer invasion related to MLK3 mutations. A reasonable hypothesis for the IQ antitumor mechanism would be the involvement of signaling pathways mediat ing its modulation of Wnt signaling [74] , which would reaffirm data presented by other studies [67,77] . The Wnt pathway in turn, is related to the p53 pathway (via apoptosis), and published literature has demonstrated its mediation of the apoptosisinducing action of IQ [73] .…”
Section: Antitumor Mechanisms Of Iqsupporting
confidence: 69%
See 2 more Smart Citations
“…It described new Wnt pathway regulation mechanisms, which may be responsible for the induction of colorectal cancer invasion related to MLK3 mutations. A reasonable hypothesis for the IQ antitumor mechanism would be the involvement of signaling pathways mediat ing its modulation of Wnt signaling [74] , which would reaffirm data presented by other studies [67,77] . The Wnt pathway in turn, is related to the p53 pathway (via apoptosis), and published literature has demonstrated its mediation of the apoptosisinducing action of IQ [73] .…”
Section: Antitumor Mechanisms Of Iqsupporting
confidence: 69%
“…Furthermore, IQ inhibited the phosphorylation of extracellular signalregulated kinase (ERK) and promoted the phosphorylation of cJun Nterminal kinase (JuNK). In vivo, IQ inhibited xenograft growth in nude mice [74] .…”
Section: Pancreatic Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…ERK1/2 phosphorylation was increased by PDGF‐BB in this study and IQC attenuated PDGF‐BB‐stimulated phosphorylation of these proteins. The same results were reported by Chen in the study of pancreatic cancer that IQC inhibited the progression of pancreatic cancer in vivo and in vitro by regulating the ERK1/2 signalling pathway . Therefore, these findings indicated that ERK1/2 likely synergized with Akt/GSK3β signalling pathway to regulate PASMCs proliferation.…”
Section: Discussionsupporting
confidence: 85%
“…The same results were reported by Chen in the study of pancreatic cancer that IQC inhibited the progression of pancreatic cancer in vivo and in vitro by regulating the ERK1/2 signalling pathway. 33 Therefore, these findings indicated that ERK1/2 likely synergized with Akt/GSK3β signalling pathway to regulate PASMCs proliferation. In summary, the present study showed that IQC alleviated the process of PAH through inhibiting PASMCs proliferation and pulmonary vascular remodelling.…”
Section: Discussionmentioning
confidence: 78%